Salicylanilide carbamates: Promising antibacterial agents with high in vitro activity against methicillin-resistant Staphylococcus aureus (MRSA) - Zadrazilova, Iveta; Pospisilova, Sarka; Masarikova, Martina; Imramovsky, Ales; Ferriz, Juana Monreal; Vinsova, Jarmila; Cizek, Alois; Jampilek, Josef (European journal of pharmaceutical sciences, 2015)
A series of twenty-one salicylanilide N-alkylcarbamates was assessed for novel antibacterial characteristics against three clinical isolates of methicillin-resistant Staphylococcus aureus (MRSA) and S. aureus ATCC 29213 as the reference and quality control strain. The minimum inhibitory concentration was determined by the broth dilution micro-method with subsequent subcultivation of aliquots to assess minimum bactericidal concentration. The bactericidal kinetics was established by time-kill assay. Ampicillin, ciprofloxacin and vancomycin were used as reference antibacterial drugs. All the tested compounds exhibited highly potent anti-MRSA activity (⩽ 0.008-4 μg/mL) comparable or up to 250× higher than that of vancomycin, the standard in the treatment of serious MRSA infections. 4-Chloro-2-(3,4-dichlorophenylcarbamoyl)phenyl butylcarbamate and 4-chloro-2-(3,4-dichlorophenylcarbamoyl)phenyl ethylcarbamate were the most active compounds. In most cases, compounds provided reliable bacteriostatic activity, except for 4-chloro-2-(4-chlorophenylcarbamoyl)phenyl decylcarbamate exhibiting bactericidal effect at 8h (for clinical isolate of MRSA 63718) and at 24h (for clinical isolates of MRSA SA 630 and MRSA SA 3202) at 4× MIC. Structure-activity relationships are discussed.
Keywords: Microbial Sensitivity Tests; buněčné linie; Time-kill assay; salicylanilidy; MRSA; Salicylanilides; mikrobiální testy citlivosti; methicilin rezistentní Staphylococcus aureus; Humans; Cell Line; Anti-Bacterial Agents; Methicillin-Resistant Staphylococcus aureus; lidé; Alkylcarbamates; antibakteriální látky; Antibacterial activity; Structure–activity relationships